Health literacy and hand hygiene practice: A factor analysis approach - Suriani Hassan; Nur Idzatul Insyirah Mohamad Isa; Sarimah Surianshah; Darmesah Gabda; Khadizah Ghazali; Chin Su Na; Siti Rahayu Mohd Hashim (Faculty of Science and Natural Resources, 2021)
The aim of this study is to identify the factors associated with health literacy and hand hygiene practice. This study also would like to examine the existence of gender differences for factors associated with health literacy and hand hygiene practice. Questionnaire was used to collect the data. Number of respondents for this study was 302. The methodology used in this study were analysis factor, normality test and non-parametric technique using Mann-Whitney test. The results showed five factors associated with health literacy and hand hygiene practice extracted using analysis factor. The Mann-Whitney test results showed there was no mean rank difference between male and female respondents of each factor associated with health literacy and hand hygiene practice.